Class A CpG Oligonucleotide Priming Rescues Mice from Septic Shock via Activation of Platelet-Activating Factor Acetylhydrolase - Yamamoto, Yoshinari; Sugimura, Ryu; Watanabe, Takafumi; Shigemori, Suguru; Okajima, Takuma; Nigar, Shireen; Namai, Fu; Sato, Takashi; Ogita, Tasuku; Shimosato, Takeshi (Frontiers in Immunology, 2017)
Sepsis is a life-threatening, overwhelming immune response to infection with high morbidity and mortality. Inflammatory response and blood clotting are caused by sepsis, which induces serious organ damage and death from shock. As a mechanism of pathogenesis, platelet-activating factor (PAF) induces excessive inflammatory responses and blood clotting. In this study, we demonstrate that a Class A CpG oligodeoxynucleotide (CpG-A1585) strongly induced PAF-acetylhydrolase, which generates lyso-PAF. CpG-A1585 rescued mice from acute lethal shock and decreased fibrin deposition, a hallmark of PAF-induced disseminated intravascular coagulation. Furthermore, CpG-A1585 improved endotoxin shock induced by lipopolysaccharide, which comprises the cell wall of Gram-negative bacteria and inhibits inflammatory responses induced by cytokines such as interleukin-6 and tumor necrosis factor-α. These results suggest that CpG-A1585 is a potential therapeutic target to prevent sepsis-related induction of PAF.